Bradykinin Induces TRPV1 Exocytotic Recruitment in Peptidergic Nociceptors - Mathivanan, Sakthikumar; Devesa, Isabel; Changeux, Jean-Pierre; Ferrer-Montiel, Antonio (Frontiers in Pharmacology, 2016)
Transient receptor potential vanilloid I (TRPV1) sensitization in peripheral nociceptors is a prominent phenomenon that occurs in inflammatory pain conditions. Pro-algesic agents can potentiate TRPV1 activity in nociceptors through both stimulation of its channel gating and mobilization of channels to the neuronal surface in a context dependent manner. A recent study reported that ATP-induced TRPV1 sensitization in peptidergic nociceptors involves the exocytotic release of channels trafficked by large dense core vesicles (LDCVs) that cargo alpha-calcitonin gene related peptide alpha (αCGRP). We hypothesized that, similar to ATP, bradykinin may also use different mechanisms to sensitize TRPV1 channels in peptidergic and non-peptidergic nociceptors. We found that bradykinin notably enhances the excitability of peptidergic nociceptors, and sensitizes TRPV1, primarily through the bradykinin receptor 2 pathway. Notably, bradykinin sensitization of TRPV1 in peptidergic nociceptors was significantly blocked by inhibiting Ca2+-dependent neuronal exocytosis. In addition, silencing αCGRP gene expression, but not substance P, drastically reduced bradykinin-induced TRPV1 sensitization in peptidergic nociceptors. Taken together, these findings indicate that bradykinin-induced sensitization of TRPV1 in peptidergic nociceptors is partially mediated by the exocytotic mobilization of new channels trafficked by αCGRP-loaded LDCVs to the neuronal membrane. Our findings further imply a central role of αCGRP peptidergic nociceptors in peripheral algesic sensitization, and substantiate that inhibition of LDCVs exocytosis is a valuable therapeutic strategy to treat pain, as it concurrently reduces the release of pro-inflammatory peptides and the membrane recruitment of thermoTRP channels.